Make a laboratory from a galley bench: Studies in honor of Professor Géza Finszter (Academic Journal of Internal Affairs, 2016)
This study volume was published in honor of Professor Géza Finszter's 70th birthday. The title of the volume refers to the turning point in the professor’s career when he began practicing law at the State Security Service.
Keywords: Géza Finszter; career; study volume